Metabolite Profiling and Transcriptome Analysis Explains Difference in Accumulation of Bioactive Constituents in Licorice (Glycyrrhiza uralensis) Under Salt Stress - Wang, Chengcheng; Chen, Lihong; Cai, Zhichen; Chen, Cuihua; Liu, Zixiu; Liu, Shengjin; Zou, Lisi; Tan, Mengxia; Chen, Jiali; Liu, Xunhong; Mei, Yuqi; Wei, Lifang; et al. (Frontiers in Plant Science, 2021)
Salinity stress significantly affects the contents of bioactive constituents in licorice Glycyrrhiza uralensis. To elucidate the molecular mechanism underlying the difference in the accumulation of these constituents under sodium chloride (NaCl, salt) stress, licorice seedlings were treated with NaCl and then subjected to an integrated transcriptomic and metabolite profiling analysis. The transcriptomic analysis results identified 3,664 differentially expressed genes (DEGs) including transcription factor family MYB and basic helix-loop-helix (bHLH). Most DEGs were involved in flavonoid and terpenoid biosynthesis pathways. In addition, 121 compounds including a triterpenoid and five classes of flavonoids (isoflavone, flavone, flavanone, isoflavan, and chalcone) were identified, and their relative levels were compared between the stressed and control groups using data from the ultrafast liquid chromatography (UFLC)–triple quadrupole–time of flight–tandem mass spectrometry (TOF–MS/MS) analysis. Putative biosynthesis networks of the flavonoids and triterpenoids were created and combined with structural DEGs such as phenylalanine ammonia-lyase (PAL), 4-coumarate-CoA ligase [4CL], cinnamate 4-hydroxylase [C4H], chalcone synthase [CHS], chalcone-flavanone isomerase [CHI], and flavonoid-3′,5′ hydroxylase (F3′,5′H) for flavonoids, and CYP88D6 and CYP72A154 for glycyrrhizin biosynthesis. Notably, significant upregulation of UDP-glycosyltransferase genes (UGT) in salt-stressed licorice indicated that postmodification of glycosyltransferase may participate in downstream biosynthesis of flavonoid glycosides and triterpenoid saponins. Accordingly, the expression trend of the DEGs is positively correlated with the accumulation of glycosides. Our study findings indicate that key DEGs and crucial UGT genes co-regulate flavonoid and saponin biosynthesis in licorice under salt stress.